Comparing Investigation Between Bilateral Partial Laminectomy and Posterior Lumbar Interbody Fusion for Mild Degenerative Spondylolisthesis. Issue 7 (August 2021) - Sugiura, Tsuyoshi; Okuda, Shinya; Takenaka, Shota; Nagamoto, Yukitaka; Matsumoto, Tomiya; Takahashi, Yoshifumi; Iwasaki, Motoki
Abstract : Study Design: A retrospective comparative study. Objective: The present study aims to compare the surgical outcomes between bilateral partial laminectomy (BPL) and posterior lumbar interbody fusion (PLIF) in patients with mild degree of slippage. Summary of Background Data: To date, there have not been established surgical procedures for patients with mild degree of slippage. Moreover, sufficient studies that have compared surgical outcomes between BPL and PLIF are very few. Materials and Methods: In this retrospective study, the authors enrolled 202 consecutive patients with degenerative spondylolisthesis with slippage at L3 or L4 of >3% who underwent spine surgery between 2005 and 2015. Patients were grouped into those who underwent single-segment PLIF (n=106) and those who underwent BPL (n=51). To adjust for potential confounders, the inverse probability of treatment weighting based on the propensity score was used. Surgical outcomes were compared between the BPL and PLIF groups. The threshold age for the final recovery rate of >70% was evaluated using receiver operating characteristic curve analyses to assess the limit of age to achieve good outcomes. Patients who underwent reoperation in both groups were also evaluated. Results: Operation time and blood loss were significantly lower in the BPL group. The final recovery rate was similar between the groups without age stratification. The cutoff age to achieve a final recovery rate of >70% was 75 years in the PLIF group, and the final recovery rate was significantly higher in the PLIF group than in the BPL group in patients aged less than 75 years but not in patients aged 75 years or older. In addition, the reoperation rate was similar between groups, and all reoperations in the PLIF group were for adjacent segment disease. Conclusions: BPL is one of the useful options in patients with mild degenerative spondylolisthesis, particularly in patients aged more than 75 years.